AN ANALYSIS OF THE FUNCTIONING OF SPEECH ACTS IN FRENCH FILM DIALOGUES (Journal of Foreign Language Studies, 2024)
This study attempts to analyse French film dialogues in which speech acts are manipulated by the dialogue writer to create the atmosphere of the film and influence the emotional state of the viewers. The functioning of speech acts was studied in correlation with the informational contents of the message and the communication situation. While speech acts have been studied as signifiers of axiological connotation in certain film scenes, their felicity conditions are considered as essential elements that create the comic effects intended by the dialogue writer. This study clarifies the functioning of speech acts in film dialogues and offers some suggestions for screen translation, particularly dubbing or subtitling.
Keywords: functioning; film; dialogue; analysis; speech act